Front Cover: Mechanistic Insights into Light‐Activated Catalysis for Water Oxidation (Eur. J. Inorg. Chem. 15/2019). Issue 15 (10th April 2019) - Natali, Mirco; Nastasi, Francesco; Puntoriero, Fausto; Sartorel, Andrea
Abstract : The Front Cover shows a sundial from Vannes (Brittany region, France), on which the hours of the day have been replaced by the timescale of the photocatalytic cycle of water oxidation, spanning from femtoseconds to seconds (picture taken by Lisa Bissacco, picture edited by Fausto Puntoriero). More information can be found in theMinireview by M. Natali, A. Sartorel et al. For more on the story behind the cover research, see theCover Profile .